Caring efficacy: nurses’ perceptions and relationships with work-related factors: Caring efficacy among nurses - Aviles Gonzalez, Cesar Ivan; Galletta, Maura; Chessa, Elsa; Melis, Paola; Contu, Paolo; Jimenez Herrera, Maria Francisca (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Caring nursing practice is central aspect of quality of services. It is important to assess nurses’ caring experience in terms of perceived caring efficacy to make them aware of their outcomes and improve their strategies. The aims of the study was to analyze: (1) the caring efficacy level, (2) differences between the caring efficacy levels concerning  positive and negative work attitudes, (3) individual and organizational predictors of perceived caring efficacy. Methods: 200 nurses were recruited from a University Hospital in Southern Italy. A self-reported questionnaire was administered. T-test was performed to analyze differences between caring efficacy levels concerning outcomes variables. Regression analysis was carried out to examine how some work factors were related to perceived caring efficacy. Results: Participants referred high confidence to care (CC) for 55%, and low doubts and concerns (DC) for 72.9%. Nurses who had low DC had lower emotional exhaustion than nurses with moderate DC. Nurses with low DC had higher job satisfaction than nurses with high DC. Regarding CC levels, there were no differences between mean values for both attitudes at work. The emotional dissonance significantly predicted DC and CC. The supervisor support had a negative link with emotional dissonance, which in turn was negatively related to CC. Conclusions: Education and training should be addressed to reduce doubts and concerns to care and improve the ability to manage emotions. A work environment that value caring and give support in managing emotions can reduce emotional dissonance and improve caring self-efficacy.